Dust emission and star formation in the Stephan's Quintet compact group of galaxies - Natale, Giovanni (2010)
Understanding the intergalactic medium (IGM) gas cooling processes, which are necessary to fuel star formation in galaxies, and the effect of galaxy--galaxy and galaxy--IGM interactions, which modify stellar and gas distributions of galaxies in groups and clusters, is vital to construct realistic models of galaxy formation and evolution. The Stephan's Quintet (SQ) compact group of galaxies is a natural laboratory for studying these phenomena because the galaxies of this group are heavily interacting between each other and with the group IGM. Furthermore its vicinity allows to study the details of the interaction phenomena, which are believed to be much more common in the early universe, and its compactness on the sky permits studies of diffuse components associated with the group IGM. In this thesis we present an analysis of a comprehensive set of MIR/FIR observations of Stephan's Quintet, taken with the Spitzer Space Observatory. The emission seen at these wavelengths is produced by dust particles and can be used to trace star formation events, AGN activity and also hot gas cooling, in the case dust emission is powered by collisions between plasma particles and dust ...
Keywords: Hochschulschrift; Galaxiengruppe; Sternentstehung; Staubemission